Intertextos franceses en la narrativa de Horacio Quiroga - Silvia Antúnez, Silvia Antúnez (2023)
This essay focuses on the french intertexts in Horacio Quiroga’s narrative, especially in fin de siècle writers such as Paul Verlaine and Guy de Maupassant, with whom he shares a decadent aesthetic. Although Quiroga’s work has already been studied in relation to those of Edgar Allan Poe and Rudyard Kipling, it has not been linked yet to the french authors of the last third of the 19th century, who were extremely important in Uruguay to Quiroga’s generation, the Generación del Novecientos. The transversal analysis suggested by the intertexts runs through his narrations taking as a starting point the little-known short story “Las voces queridas que se han callado”, to which other texts by the author are gradually associated.